Frontal cerebral blood flow change associated with infant-directed speech. Issue 2 (11th August 2006) - Saito, Y; Aoyama, S; Kondo, T; Fukumoto, R; Konishi, N; Nakamura, K; Kobayashi, M; Toshima, T
Abstract : Objective: To examine the auditory perception of maternal utterances by neonates using near-infrared spectroscopy (NIRS). Methods: Twenty full-term, healthy neonates were included in this study. The neonates were tested in their cribs while they slept in a silent room. First, two probe holders were placed on the left and right sides of the forehead over the eyebrows using double-sided adhesive tape. The neonates were then exposed to auditory stimuli in the form of infant-directed speech (IDS) or adult-directed speech (ADS), sampled from each of the mothers, through an external auditory speaker. Results: A 2 (stimulus: IDS and ADS) × 2 (recording site: channel 1 (right side) and channel 2 (left side)) analysis of variance for these relative oxygenated haemoglobin values showed that IDS (Mean = 0.25) increased brain function significantly (F = 3.51) more than ADS (Mean = −0.26). Conclusions: IDS significantly increased brain function compared with ADS. These results suggest that the emotional tone of maternal utterances could have a role in activating the brains of neonates to attend to the utterances, even while sleeping.